PENGARUH PENGGUNAAN ANGGARAN DAN GAYA KEPEMIMPINAN TERHADAP HUBUNGAN PERUBAHAN STRATEGIK DENGAN KINERJA ORGANISASI - Murni`, Rochiyati (Jurnal Analisis Bisnis Ekonomi, 2007)
This research aim to test influence of strategic change to organizational performance at company using budget by interactive compared using budget diagnostically,. Second target is to know influence of strategic change to organizational performance at company using style leadership of consideration with company using style leadership of structure initiating. Organizational performance represent a measuring instrument used to measure storey, level efficacy of management. Company often make a change strategic to reach optimal performance. This research take manufacturing business sample exist in Magelang, by propagating equatedto middle storey; level manager from each company. Sample selected with method of convenience sampling, and got by 40 respondent. Result of research express that strategic change have an effect on positive to performance when company use budget by interactive. Examination to both hypothesis expressing that strategic change will be more have an effect on when ompany use style leadership of consideration than structure initiating. As narrow; tight as research region which only in Magelang cause result of this research less earn generalizing for boarder region, so that for research herei in afte shall be conducted by taking sample with broarder region.